PARENTAL AUTHORITY IN SPOUSE SELECTION: PERSPECTIVES ON ISLAMIC LAW AND CHILD PROTECTION REGULATIONS - Muhammadong, Muhammadong (Yayasan Nuraini Ibrahim Mandiri, 2026)
Marriage is an important part of a person's life, and in some cultures, parents have a lot of power over who their children marry. Islamic law in Indonesia lets parents have a voice in who their children marry, but child protection laws stress that minors have the freedom to pick their own partners. This study seeks to evaluate the legal authority of parents in selecting their children's spouses, through an analysis of Islamic law and child protection rules in Indonesia. This research employs a qualitative methodology, incorporating a literature review from many legal sources, including Islamic law texts, Indonesian legislation, and perspectives from legal and child protection professionals. The results show that Islamic law gives parents the right to advise their children on who to marry, while Indonesian child protection laws put more emphasis on the kid's freedom to pick their spouse freely and without pressure. In conclusion, even though Islamic law and child protection laws don't agree on everything, they both stress the need of balancing the rights of parents and children when choosing a life partner.